Role of Success in Education - Janulaitienė, Nijolė (Acta Paedagogica Vilnensia, 1993)
The article describes the results of the pedagogical experiment, which involved 403 school kids in Kaunas, with particular emphasis on success. Most of the surveyed students were academically inferior, pedagogically neglected, so they could first experience success only in after-school activities. Having in mind that most of these teenagers were bored with the school, class teachers helped select organization or activities outside of school according to individual interests and hobbies. Although volatility of interest of teenagers when faced with the slightest failure emerged, they would quit a circle or activities, but most of those who remained, succeed not only in extracurricular activities but also improved results of their learning. The second stage of “success” methodology was the classroom activity. For pedagogically neglected students to quickly achieve better learning outcomes, the teachers of experimental schools were advised how to help students experience success as soon as possible. “Success” approach consisted of positive stimulation, differentiated requirements, rational organization of training activities, intensive teaching, coordination of classroom and with extracurricular activities. The experiment was a success. During its two years pedagogically neglected students improved in achievements, behaviour, positive changes have taken place in moral sphere. 85% of the students were removed from the list of those with education difficulties.
Keywords: pedagogical experiment; education difficulties; extracurricular activities; “success” methodology